Public Education Policies and Quality Assurance in Higher Education (2019)
This article reports on the results of the research that analyzes the mechanisms that shape the quality assurance systems of higher education in the context of Latin America. With special emphasis on Colombia, we try to highlight the, institutionally consolidated, curricular and academic trends emerged from the problems and demands of the new labor markets, framed in the capitalist globalization, as a reflection of the currently implemented public education policies.  Through the case study in Colombia and the review of institutional documents, it was found that higher education and public quality assurance policies appear as the operating device of an asymmetric international structure. In the case of Colombia, rather than difficulties in the formulation, problems are found in the implementation and execution phases, due to the inflexibility of the academic and administrative cultures of higher education institutions. Finally, it is concluded that quality assurance and accreditation contribute to the generation and organization of information for higher education systems. Public policies of quality and internationalization, in the Colombian higher education system, depend on the achievement of acceptable and productive levels of consolidation and the management of the directive and teaching authority in the midst of a quality, administrative, and institutional academic culture of favorable governance.